Endoscopic Removal of a Dental Implant From Maxillary Sinus - Dundar, Serkan; Karlidag, Turgut; Keles, Erol (Lippincott Williams & Wilkins, 2017)
The displacement of a dental implant into the maxillary sinus during surgery or after a period of use is a complication defined in the dental implant clinical practice. This complication arises primarily from inadequate bone height and peri-implant infection. Specifically, foreign objects in the maxillary sinus can cause sinusitis via impaired mucociliary flow and foreign body reactions, so they must be removed. Caldwell-Luc, transnasal, and intraoral endoscopic sinus surgeries have all been used to remove such foreign bodies and lesions from maxillary sinuses. In this article, the authors present the case of a patient whose dental implant slipped into the right maxillary sinus after a period of use and describe the endoscopic removal of said implant via an intraoral approach. The endoscopic removal of the dental implant from the maxillary sinus proved to be a safe, reliable, and minimally invasive method.
Keywords: Endoscopic sinus surgery; foreign body; implant displacement; implant migration; maxillary sinus